Preseismic changes in groundwater level and volumetric strain associated with earthquake swarms off the east coast of the Izu Peninsula, Japan - Koizumi, Naoji; Tsukuda, Eikichi; Kamigaichi, Osamu; Matsumoto, Norio; Takahashi, Makoto; Sato, Tsutomu (Geophysical research letters, 1999)
We have observed the groundwater level at Omuroyama‐kita (OMR) well on the Izu Peninsula, Japan since October 1994. During the observation period, there were four earthquake swarms. We detected one or two preseismic groundwater level changes together with preseismic crustal deformation recorded at the other nearby stations. Therefore those preseismic groundwater level changes are considered to be caused by crustal deformation or volumetric strain changes. The crustal deformations are inferred to be caused by the magmatic dike intrusion, which is a possible source of the earthquake swarms off the east coast of the Izu Peninsula.